Implementasi Sistem Informasi Manajemen Aset Kelompok Ternak Ikan Hias Sumedang Menggunakan Metode Prototype - Fasya Zahira Badeni; Agun Guntara; Irfan Fadil (FKOM UNIKU, 2024)
This study develops and implements an Asset Management Information System for Ornamental Fish Breeding Groups in Sumedang using the prototype method. The objective is to streamline the management of asset data, inventory, and asset condition monitoring in an efficient and organized manner. The prototype method was selected because it promotes intensive interaction between developers and users, enabling quick identification and resolution of needs and issues. The development stages include communication, planning, design modeling, prototype creation, and system implementation. This system features the ability to record and monitor assets, track asset loans, and log asset maintenance, thereby generating accurate reports and minimizing data errors. It is expected that this information system will help ornamental fish breeding groups in Sumedang manage their assets more effectively, boost productivity, and support the sustainability of their business.